Norms on intuitionistic fuzzy multigroups - Rasuli, Rasul (Yugoslav Journal of Operations Research, 2021)
In this paper, we propose the notion of intuitionistic fuzzy multigroups under norms (t-norm T and t-conorm C) and study the variety of their algebraic structure. Next, we define the inverse, product, intersection and the sum of them. Also, we explored some of their properties and got the related results. Finally, under group homomorphisms, image and pre image of them are introduced and investigated.